The Challenges of Creating a Global Health Resource Tracking System - Eiseman, Elisa (RAND Corporation, 2005)
The RAND Corporation conducted interviews, consulted with experts, and carried out detailed analyses of existing tracking systems that focus on health resources flowing to and within developing countries, the objective being to determine how to provide a truly global health resource tracking system that will provide comprehensive, accurate, up-to-date data for policymakers and other users and will address the current systems' limitations.